Improving Inservice Teacher Workshops in Florida - Martha C. Monroe; Jenny Seitz; Shruti Agrawal; Michelle Aldridge; Sheda Morshed; Elizabeth Swiman; Vicki Crisp (EDIS, 2005)
To increase their usefulness to educators, workshop facilitators should be familiar with terms and concepts now used to describe Florida's professional development. These terms should be incorporated into inservice programs. This fact sheet defines the terms that are most helpful and provides suggestions for planning, advertising, delivering, and evaluating workshops to meet the needs of our teachers. Project Learning Tree (PLT) workshops are used as an example of how nonformal education facilitators could adapt their workshops to better address the new professional development system. This document is FOR 109, one of a series of the School of Forest Resources and Conservation Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date February 2005.